Trends in Teacher Monitoring Methods across Curriculum and Didaktik Traditions: Evidence from three PISA waves - Tahirsylaj, Armend (Nordic Journal of Comparative and International Education (NJCIE), 2020)
The main objectives of this study were to examine trends in teacher monitoring methods (TMMs) among a representative set of 12 curriculum and didaktik countries, using data from PISA 2009, 2012, and 2015, and the association of TMMs with students’ reading, mathematics, and science performance accordingly. Curriculum and didaktik education traditions frame the study theoretically, while quantitative research methods are used, consisting of a two-sample difference of proportion test and hierarchical linear modelling. The findings suggest that across the PISA waves, the control over teachers is growing across all countries and in all three subject domains and four TMMs. However, the proportion of students in schools where any of the TMMs are used is higher and more statistically significant for curriculum than for didaktik countries. Student tests, teacher peer review, and principal observation are much more common TMMs than external inspector observation across all countries. Nevertheless, the use of external inspector observation is very low in several didaktik countries, and in the case of Finland almost inexistent. Results for Sweden seem to be over-reported as in previous survey work it was found that teacher self-assessment is the most common TMM, however, teacher self-assessment is not a variable included in the PISA survey. The results from within-country hierarchical linear models (HLMs) of associations of TMMs with students’ reading (2009), mathematics (2012), and science (2015) performance in PISA show mixed, and at times relatively large, effects from country to country and across three PISA waves, and interestingly the associations had diminished by PISA 2015. Adding a more diverse set of questions to PISA contextual questionnaires is warranted for results to be more meaningful and representative across more countries.